2015
DOI: 10.1128/jb.02113-14
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Cell-to-Cell DNA Transfer in Thermus spp. Is Insensitive to Argonaute-Mediated Interference

Abstract: bHorizontal gene transfer drives the rapid evolution of bacterial populations. Classical processes that promote the lateral flow of genetic information are conserved throughout the prokaryotic world. However, some species have nonconserved transfer mechanisms that are not well known. This is the case for the ancient extreme thermophile Thermus thermophilus. In this work, we show that T. thermophilus strains are capable of exchanging large DNA fragments by a novel mechanism that requires cell-tocell contacts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…On the other hand efficient transjugation was detected between ΔTTC1879:: kat and ΔpilA :: hyg single mutants (Fig 1, bar n° 2). As two strains defective in competence cannot mate [16,19], this result confirmed that the product of TTC1879 was not involved in natural competence, and provides evidence that TTC1879 is required for DNA donation in transjugation, and not for DNA acquisition. The product of TTC1879 was thus designated the T ransjugation D onor T ranslocase A (TdtA).…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…On the other hand efficient transjugation was detected between ΔTTC1879:: kat and ΔpilA :: hyg single mutants (Fig 1, bar n° 2). As two strains defective in competence cannot mate [16,19], this result confirmed that the product of TTC1879 was not involved in natural competence, and provides evidence that TTC1879 is required for DNA donation in transjugation, and not for DNA acquisition. The product of TTC1879 was thus designated the T ransjugation D onor T ranslocase A (TdtA).…”
Section: Resultsmentioning
confidence: 66%
“…To analyze the role of TTC1879 in DNA donation (pushing step) we introduced the ΔTTC1879:: kat mutation into a ΔpilA4 background, which is unable to serve as a recipient in transjugation assays [16], and mated it with a wild type strain labeled with hygromycin (Hyg) resistance. No transjugants were generated in this mating (Fig 1, bar n° 3), implying that the ΔTTC1879:: kat mutant cannot donate DNA in transjugation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations